The Effect of Three Different Shoeing Conditions on Tendon Strain in the Thoroughbred Forelimb. (September 2015) - Ault, B.; Starling, G.; Parkes, R.; Pfau, T.; Pardoe, C.; Day, P.; Bettison, C.; Weller, R.
Abstract : Reasons for performing study: Previous studies show the effect of toe or heel wedges on tendon strain but there is little understanding of the effect of other shoe types. Objectives: To quantify the effect of different shoeing conditions on the strain in the superficial digital flexor tendon (SDFT), deep digital flexor tendon (DDFT), distal check ligament (ALDDFT) and suspensory ligament (SL). Study design: Controlled experimental study. Methods: Twelve equine cadaver forelimbs were loaded onto a force plate mimicking stance phase. Markers were placed proximally and distally in each tendon structure and tracked using a motion capture system and strain was calculated. Tendon strain was determined for the following conditions: barefoot, glue on heart bar and aluminium racing plates with and without packing material. Data were analysed using a mixed effects model. Results: Significant variation in strain was observed between tendons. The DDFT had the lowest strain, then the ALDDFT, SDFT and SL. Glue on heart bar shoes significantly increased SDFT and SL strain compared to barefoot for the same leg force. Aluminium racing plates without packing material increased ALDDFT and SDFT strain and with packing material increased ALDDFT and SL. Conclusions: Shoe selection should be based on minimising strain in the tendon with greatest injury risk. Aluminium racing plates with packing material may be most appropriate for the majority of racehorses as they do not significantly increase SDFT strain. Ethical animal research: Research ethics committee oversight not currently required by this conference: the study was performed on material obtained from an abattoir.Source of funding: The authors would like to thank the Horserace Betting Levy Board for their support of this project.Competing interests: None declared.Acknowledgements: We thank Peter Day, Carl Bettison, Chris Pardoe, Marianna Biggi and Emily Sparkes.